Penilaian Penggunaan Teknologi Informasi Dalam Pengelolaan Keuangan Daerah Dan Dampaknya Terhadap Kinerja Pelayanan Publik Di Indonesia - Kardina, Mutia; Frinaldi, Aldri; Asnil, Asnil; Putri, Nora Eka (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
This research aims to assess the use of information technology in regional financial management and its impact on public service performance in Indonesia. The background to this research refers to the importance of transparency and efficiency in regional financial management which can be improved through the application of information technology. The research method used is a literature study, which involves collecting and analyzing data from various relevant sources, including journals and research reports related to the implementation of information technology in the public sector. The research results show that the use of information technology in regional financial management has a positive impact on public service performance. These findings include increased efficiency in budget management, transparency of financial reports, and public satisfaction with public services. However, challenges in implementing information technology still exist, such as limited infrastructure and human resource training.